E-Economic Transactions among Muslim Women in Contemporary Northern Nigeria - Muhammad, Adamu Abubakar; Aliyu, Shafa’atu Ahmad; Ardo, Adam Muhammad; Shariff , Ikilima Abubakar; Muhammed , Yakubu Zulaihat (Abdurrauf Law and Sharia, 2024)
The emergence of digital technology and e-commerce has provided uncountable access of wealth and novel economic prospects to women worldwide, particularly Muslim women residing in Northern Nigeria. This study investigates the ways in which Muslim women engage in e-commerce within an area that has historically been influenced by conventional conservative religious and cultural standards. Through an analysis of their participation in virtual enterprises, the research underscores the distinct socio-cultural and religious elements impacting their e-commerce endeavors. It also discusses the difficulties they have, like their lack of access to technology, low levels of digital literacy, and financial marginalization. The study uses secondary data from government papers, academic literature, and case studies as part of a qualitative research technique. Women who were involved in e-commerce were interviewed, and data from previous surveys was examined to offer insights into the trends of participation and the barriers faced. The results indicate that although e-commerce presents a great opportunity for economic empowerment, a number of obstacles prevent full engagement. These include the necessity for financial products that comply with Sharia law, societal expectations, and infrastructure constraints. The article ends with suggestions for boosting the participation of Muslim women in the digital economy, with an emphasis on advancing financial services that adhere to Sharia law, increasing digital literacy, and increasing access to technology. These tactics may encourage Muslim women to become more financially independent, which would boost the region's economy in Northern Nigeria.  Abstrak: Munculnya teknologi digital dan e-commerce telah memberikan akses kekayaan dan prospek ekonomi baru yang tak terhitung jumlahnya bagi perempuan di seluruh dunia, terutama perempuan Muslim yang tinggal di Nigeria Utara. Studi ini menyelidiki cara-cara di mana wanita Muslim terlibat dalam e-commerce dalam area yang secara historis dipengaruhi oleh standar agama dan budaya konservatif konvensional. Melalui analisis partisipasi mereka dalam perusahaan virtual, penelitian ini menggarisbawahi elemen sosial-budaya dan agama yang berbeda yang memengaruhi upaya e-commerce mereka. Ini juga membahas kesulitan yang mereka hadapi, seperti kurangnya akses ke teknologi, tingkat literasi digital yang rendah, dan marginalisasi keuangan. Studi ini menggunakan data sekunder dari makalah pemerintah, literatur akademik, dan studi kasus sebagai bagian dari teknik penelitian kualitatif. Wanita yang terlibat dalam e-commerce diwawancarai, dan data dari survei sebelumnya diperiksa untuk menawarkan wawasan tentang tren partisipasi dan hambatan yang dihadapi. Hasil penelitian menunjukkan bahwa meskipun e-commerce menghadirkan peluang besar untuk pemberdayaan ekonomi, sejumlah hambatan menghalangi keterlibatan penuh. Ini termasuk perlunya produk keuangan yang sesuai dengan hukum Syariah, harapan masyarakat, dan kendala infrastruktur. Artikel diakhiri dengan saran untuk meningkatkan partisipasi perempuan Muslim dalam ekonomi digital, dengan penekanan pada memajukan layanan keuangan yang menganut hukum Syariah, meningkatkan literasi digital, dan meningkatkan akses ke teknologi. Taktik ini dapat mendorong wanita Muslim untuk menjadi lebih mandiri secara finansial, yang akan meningkatkan ekonomi kawasan di Nigeria Utara. Kata Kunci: Transaksi E-Ekonomi; Wanita Muslim; Nigeria Utara